Principal Leadership and Achievement Motivation on Teacher Performance - Hardiyana, Aan (East Asian Journal of Multidisciplinary Research, 2024)
This research investigates the influence of principal leadership and achievement motivation on teacher performance. Quantitative methods are used to survey 57 high school teachers in Bandung. Sampling was carried out purposively among teachers willing to participate in the research. Data were collected and analyzed using PLS structural equation modeling (SEM). Research findings show a significant influence of principal leadership and achievement motivation on teacher performance. The research results highlight the importance of effective principal leadership and strong teacher achievement motivation in improving the performance of high school teachers in Bandung. The implication of this research is the need to pay attention to these factors to improve the quality of education in high school. Future research could involve additional variables for a more comprehensive understanding.